Plagioclase Fractionation On The Holocene Volcanic Rocks Evolution In West Halmahera Regency - Ipranta Ipranta; Ronaldo Irzon (Pusat Survei Geologi, 2019)
The tectonic complexity in the Maluku region is caused by the interaction of the three main platesin this area, namely: the Philippine Plate, the Australian Plate, and the Eurasian Plate. The origin of volcanic rock-forming material from Jailolo Mount., Sahu Mount., Gamkonora Mount., and Ibu Mount. in West Halmahera Regency is the aim of this study. Petrographic, trace elements, rare earth elements analysis are also used to study rock formation processes and correlations between sample groups. Bipolar microscope and Inductively Coupled Plasma - Mass Spectrometry of the Center for Geological Survey Laboratory are the analytical devices used in this study. Almost all samples are classified as andesite based on the comparison of the quartz, K-feldspar, and plagioclase compositions. There is a possibility of mixing between oceanic crust and continental crust of the studied Holocene volcanic which is indicated by La/Yb versus Nb/La diagrams. Fractional crystallization is considered more influential in rock formation compared to partial melting. The effect of plagioclase fractionation on the four volcanic rock groups is shown by the Y versus Sr/Y diagram and rare earth spider diagram patterns. Increased levels of rare earths in samples from G. Gamkonora and G. Sahu are strongly influenced by crystallization of plagioclase during rock formation.Key words: volcanic rocks, petrography, geochemistry, West Halmahera